Retention properties of the Agulhas bank and their relevance to the chokka squid life cycle. (August 2022) - Jacobs, Zoe; Kelly, Stephen; Jebri, Fatma; Roberts, Michael; Srokosz, Meric; Sauer, Warwick; Hancke, Lisa; Popova, Ekaterina
Abstract: Retention is thought to be a crucial component required to create a favourable habitat for coastal pelagic species. It is vital for the survival of 'chokka' squid ( Loligo reynaudii ), which is a fishery that supports thousands of people living in the Eastern Cape of South Africa. After chokka spawn, retention on the Agulhas Bank is crucial to prevent starvation in the early life stages. Using a high-resolution ocean model, this study quantifies retention properties of the Agulhas Bank most relevant to the chokka squid. We estimate the proportion of virtual Lagrangian particles, representing paralarvae, that are retained on the Agulhas Bank within 30 days after being released from the main chokka squid spawning sites. Over an 18-year period (1995–2013), considerable variability is found on seasonal and interannual timescales, with the greatest retention occurring for particles released further to the west. The greater losses for the easternmost release sites are due to increased interaction with the Agulhas Current. While 90–100% retention is the most common scenario, high loss (>50%) events are also apparent and are associated with different variability modes of the Agulhas Current. These variability modes include i) meanders that cause offshore flow at the northeast edge of the Bank, ii) the presence of a fast, onshore branch of the Agulhas Current rapidly advecting the particles off the Bank further west (associated with a Natal Pulse) and iii) an Agulhas Current positioned further south of the Bank leading to an offshore flow from the eastern Agulhas Bank. The third variability mode usually occurs 1–2 months after the passage of a Natal Pulse or meander. However, 1–2 weeks after the passage of a Natal Pulse, retention increases, so the timing of these events relative to particle release is crucial. This shows that the key to understanding paralarvae retention lies both in the occurrence of these dynamic features and in their timing relative to the spawning events.